Værkstedstradition, mesterrelation og bygherre: Studier af Danmarks senmiddelalderlige styltetårne - Bertelsen, Thomas (Hikuin, 2003)
Studies of the late medieval stilt towers of Denmark By Thomas Bertelsen The research is dealing with a characteristic late medieval type of church towers, especially spread in Eastern Jutland and dating back to about 1450-1550. The type differs from traditional towers by having no tower room, but instead one or – in infrequent cases – more open arcades, hence the name »stilt towers« (fig. 1, 2). Within the present borders of Denmark 54 out of 59 stilt towers, completely or partly preserved, have been investigated, mainly situated within the medieval Diocese of Århus (fig. 3). Most of the towers can be divided into two main types, each of them representing a building tradition. The largest group mainly comprises of towers within the area of Djursland, but also south of Århus. These towers are of a very slight construction, with very high arcades and only one storey for the bell (fig. 1). The second group is mainly fund about and between the inlets of Randers and Mariager. These towers are more strongly built, with very low arcades and more storeys (fig. 4). A group of towers within the area of Djursland and south of Århus can be assigned to a small group of master builders (fig. 5- 11), eg. The Tirstrup-Albøge master, who may possibly be the originator of the special building style of Danish stilt towers.